Winning Potential Customers through Online Complaint Management: A Case of Malaysian Hospitality Industry - Liew, Fionn Yin Foong (2014)
Today’s travel planners are increasingly depending on online travel reviews to facilitate their decisions on travel decisions on travel arrangement including hotel booking. In relation to this, hotel managers must carefully handle negative reviews i.e. online complaints which can impact potential customers who observe the complaint handling process on social media. This research aims to identify effective approaches of online complaint management that can serve as marketing tools which attract potential customers. To be specific, present research examines the relationship between online complaint response strategies (responsiveness, courtesy and compensation), trust and behavioral commitments (positive WOM or word of mouth and booking intention) of potential customers in the context of Malaysian hospitality industry. This research adopts a 2 (responsiveness: high/low) x 2 (courtesy: high/low) x 2 (compensation: high/low) experimental design to compare findings between nine groups of respondents (eight experimental groups and one control group). 323 respondents were exposed to one of the nine hypothetical scenarios that manipulated different combinations of levels of the response strategies in an online survey which then measured their ratings on trust, positive WOM and booking intention. Outcomes of this experimental study implies that high level of courtesy and compensation induced greater trust which lead to greater positive WOM of potential customers. These findings suggest hotel managers to put effort in online complaint management by ensuring courteous responses and providing compensation when necessary to attract potential customers.